Assessment of Electromyography in Evaluating Masseter Muscle Activity in Oral Submucous Fibrosis with Different Treatment Modalities: a Systematic Review - P., Poornachitra; T.N., Uma Maheswari (Odovtos - International Journal of Dental Sciences, 2023)
Electromyography (EMG) is used for the measurement of muscle activity to characterize the nature of muscle contraction in Oral submucous fibrosis (OSMF). Aim: To assess the efficacy of EMG in evaluating masseter muscle activity in the management of OSMF. This review identified 73 records from standard databases which were rigorously screened with eligibility criteria and 3 clinical studies were identified based on our inclusion criteria. The quality of included studies was assessed by the PEDro scale and data was synthesized with detailed characterization. The Risk of Bias assessment among studies was done using the ROBINS-I tool and a meta-analysis could not be done due to high clinical heterogeneity. Our result recommends that EMG be used as an objective prognosis assessment tool by quantifying the management of OSMF irrespective of the intervention applied. However, it is not to be considered the gold standard as of now with limited data pooled and needs to be further assessed with clinical trials. EMG can be advocated as a reliable adjunct assessment for measuring the interventional outcome of OSMF irrespective of treatment modalities.